TYPES OF EVIDENCE: A COMPARATIVE STUDY BETWEEN ISLAMIC LAW AND CIVIL PROCEDURE LAW - Siti Saenah (JURISTA: Jurnal Hukum dan Keadilan, 2020)
The writing of this article is to find answers to the main problems, namely how are the types of evidence in Islamic law and civil procedural law and how are the similarities and differences in evidence between Islamic law and civil procedural law. The results of the study, in Islamic law the types of evidence agreed upon by scholars are seven kinds, namely: confession, testimony, oath, nukul, qarinah, qasamah, and recognition of the judge. While in civil procedural law consists of five types, namely: written evidence, witnesses, confessions, suspicion, and oaths. This is because in Islamic law regarding oaths are classified into several types as evidence. The difference lies in the evidence, and the main evidence where in Islamic law is recognition. Whereas in civil procedural law is written evidence. This is because in ancient times people who were good at writing were very few so that this written evidence was not so popular, in Islamic shari'a too.